Nanotechnological interventions in sustainable agriculture (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
The major problems associated with agriculture are the sustainable management of natural resources. With technological innovations and capital investments crop production has increased but care of ecological systems has not been given priorities and thus created imbalance in the natural cycle of the soil, crop productivity, salinization, moisture content, organic matter and seeping problems of pesticides. Nanotechnology provides a plethora of techniques to face the challenges of increasing population and food production, at the same time taking care of the environment, and has opened new avenues for sustainable agriculture. It has a myriad of applications, whether it is in medicine, electronics, agriculture, food technology, environment, cosmetics. Worldwide, there is improvement in sensing which is highly important in agriculture. Crop yield mainly depends on soil fertility, water supply and other environmental factors. Nanotechnology has revolutionised food production commonly referred to as “green nanoagroscience” which implements green chemistry in an eco-friendly manner and using biocompatible methods, which is cost-effective. This review mainly focuses on the latest development in nanobiotechnology and their applications along with challenges in sustainable agriculture developmentand the future prospects.